Comparison of Femoral Notch Width, Shape, and Medial Tibial Plateau Concavity in Individuals with and without Anterior Cruciate Ligament Injury - Hajatpour, Nika; Mobin, Hadi K.; Gerami, Reza; Hesari, Shamim F.; Kargar, Jalal (The Journal of Knee Surgery, 2025)
Anterior cruciate ligament (ACL) injuries can occur in people of all ages and genders. Women are significantly more likely to experience them, particularly during their adolescent and young adult years. In the current study, we compared the width and shape of the femoral intercondylar notch and depth of the concavity of the medial tibial plateau in individuals with and without ACL injuries. In this cross-sectional study, 100 participants (50 in the ACL injury group and 50 in the no-ACL injury group) were included. Data on age, gender, shape (categorized as U, A, and Ω), and width (notch width [NW] and notch width index [NWI]) of the femoral intercondylar notch, and the concavity depth of the medial tibial plateau and bicondylar width (BCW) of all participants were obtained from magnetic resonance imaging (MRI) and recorded. All data were analyzed using SPSS version 21, and a significance level of <0.05 was considered. The prevalence of female gender in the ACL and no-ACL injury groups was 40% and 52%, respectively. The mean NWI and medial tibial plateau depth were significantly higher in the no-ACL injury group compared with the ACL injury group (p < 0.001). The intercondylar notch shape significantly differed between the two groups, with a higher frequency of type A notch in the ACL injury group and U shape in the no-ACL injury group (p < 0.001). Additionally, the mean NW was significantly narrower in the ACL injury group across the ≤30- and >40-year age groups (p < 0.001), although no significant difference was found in the 31- to 40-year age group (p > 0.05). Receiver operating characteristic (ROC) analysis indicated that NWI was the most predictive measure for ACL injuries (area under the curve [AUC] = 0.869), followed by NW (AUC = 0.763). BCW, however, had a lower predictive value (AUC = 0.431). Due to our findings, narrow NWI and A-shaped femoral intercondylar notch were more prevalent in the ACL injury group than the no-ACL injury group, suggesting a risk factor for ACL injuries.
Keywords: anterior cruciate ligament; femoral intercondylar notch; medial tibial plateau